Praktek Menyusui Ibu Pekerja Pabrik dan Ibu Tidak Bekerja di Kecamatan Sukoharjo Kota Kabupaten Sukoharjo - Agus Sartono (Jurnal Gizi, 2013)
Breastfeeding is the best nutrition in quantity and quality for optimally baby’s growth. A Cross sectional study combaining quatitative and qualitative approaches was conducted at Sukoharjo Kota subdistrict. The objective of this study is to investigate exclusive breast feeding practices among female factory workers and housewives and to explore internal andexternal factors influencing exclusive breast feeding practices among female factory workers. The study shows that only 9.5 % infant were exclusively breastfeeded among female factory workers, and statistical difference was found as compared to housewives. Among the workers, level of education had a significant relationship with exclusive breast feeding pattern. Factory policy does not consistenly support exclusive breast feeding practices, despite the fact that this policy may effect exclusive breast feeding practices if it is supported means of transportation and short distance to the workers houses. In addition, health personal indirectly encourages mothers to use milk formulaKeyword : Exclusive breast feeding practice – female factory workers – Cross sectional study– qualitative study.